2009
DOI: 10.1002/hlca.200900159
|View full text |Cite
|
Sign up to set email alerts
|

The Photochemical Behavior of the Uranyl Ion (UO$\rm{{_{2}^{2+}}}$): a Dimer Perspective and Outlook

Abstract: Dedicated to Jean-Claude Bünzli on the occasion of his 65th birthdayThe complex formation of uranyl (UO 2þ 2 ) with oxalic acid (HOOCÀCOOH) in acetone is studied by UV/VIS, absorption, luminescence, and excitation spectroscopy. Based on solid-state crystallographic data, we propose a dimer structure with D 2h symmetry for the complex in solution. This symmetry is vibrationally distorted to D 2 by the out-of-plane equatorial-ligand vibration. From the spectroscopic point of view, this vibration induces intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…87−89 The well-studied hydrolysis of uranyl shows dimers and trimers with bridging OH ligands existing in solution along with monomers. 90−98 The separation between the uranium atoms in these dimers is generally 0.38−0.49 nm, 85,88,89,91,92,94,95,98 which is considerably shorter than the distance observed here, indicating that Tf 2 N is a much weaker coordinating ligand. The exception is perrhenate-bridged dimers, which have U−U distances of 0.66−0.69 nm.…”
Section: Simulation Detailsmentioning
confidence: 67%
See 1 more Smart Citation
“…87−89 The well-studied hydrolysis of uranyl shows dimers and trimers with bridging OH ligands existing in solution along with monomers. 90−98 The separation between the uranium atoms in these dimers is generally 0.38−0.49 nm, 85,88,89,91,92,94,95,98 which is considerably shorter than the distance observed here, indicating that Tf 2 N is a much weaker coordinating ligand. The exception is perrhenate-bridged dimers, which have U−U distances of 0.66−0.69 nm.…”
Section: Simulation Detailsmentioning
confidence: 67%
“…The uranyl perrhenate dimeric complex in [BMIM][Tf 2 N] was not observed in UV–vis and EXAFS experiments, although the solutions used in the experiments had a very dilute concentration of uranyl (0.01–0.001 M) . Experiments have shown that perrhenate and oxalate ligands can bridge to form uranyl dimeric complexes under the correct conditions. Carboxylate and carbonate ligands can also cause dimerization. The well-studied hydrolysis of uranyl shows dimers and trimers with bridging OH ligands existing in solution along with monomers. …”
Section: Resultsmentioning
confidence: 99%
“…From the solid state structures, 37 it is expected that the most probable structure is two chelate + one unidentate binding. 20 We have studied three possible structures which are listed in Table 1 (S15-S17). From the Gibbs energy obtained by the DFT calculations, the most stable structure is S15.…”
Section: Coordination Of Uranyl(vi) Oxalatementioning
confidence: 99%
“…Our results are consistent with the previous work by G örller-Walrand and Servaes who proposed a photochemical reaction mechanism involving a 2 : 5 complex, although their study was performed in acetone and not in aqueous solution. 20 Fig. 4 The structure of the lowest-lying triplet state of uranyl(VI) oxalate 2 : 5 complex (T15).…”
Section: Photochemistry Of Uranyl(vi) Oxalate 1 : 3 and 2 : 5 Complexesmentioning
confidence: 99%
See 1 more Smart Citation